Exhaust System Muffler Volume Optimization of Light Commercial passenger Car Using Transfer Matrix Method - Mohamad, Barhm; Jalics, Károly; Kermani, Milad (International Journal of Engineering and Management Sciences, 2019)
Nowadays, the automotive industry is focused on weight and size reduction. Main advantage of this weight and size reduction are improving the fuel economy. The specific fuel consumption of a vehicle can be improved through e.g. downsizing area of heat loss, if we focus on vehicle with weight reduction. Weight reduction can be done by replacing material or by changing the size (dimensions) of components. In the present work we have focused on Audi A6 muffler, troubleshooting and optimizing the muffler by changing pipe length of inlet and outlet, also by replacing the original mesh plate to porous pipe. Based on optimization, prototype has been built with the help of 3D design tool CATIA V5 and the calculations of transmission loss (TL) have been performed by MATLAB. Plane wave-based models such as the transfer matrix method (TMM) can offer fast initial prototype solutions for muffler designers. The principles of TMM for predicting the transmission loss of a muffler was used. Result of this present study of an existing muffler has been analysed and then compared with vehicle level test observation data. Noise level have been optimized for new muffler design. Other literatures were played significant rule for validate our results.